Hak negara dan hak warga negara di era saat ini - Rahmah, Fitri Aulia; Mila, Alfi Eizatul; Rosyadi, Miroslav Rayhan (Maliki Interdisciplinary Journal, 2025)
Rights are a fundamental aspect of state life, both for the state and citizens. However, in Indonesia there is often an imbalance between the rights of the state and the rights of citizens, which triggers social conflicts and rights violations. Many citizens have not enjoyed a decent life, even though the constitution has guaranteed their basic rights. The lack of understanding of rights is a major factor in violations, both by citizens and by the state. This research aims to raise public awareness about the importance of rights fulfillment, both from the side of the state as a sovereign institution and citizens as part of a democratic system. The method used is descriptive qualitative with a literature study approach, which is sourced from the constitution, laws, and other relevant regulations. The results show the importance of the state performing its functions fairly and transparently in guaranteeing and protecting the rights of citizens, as well as asserting its rights in upholding the law, maintaining national stability, and protecting territorial sovereignty. Equitable fulfillment of rights is the key to creating a just, prosperous and democratic nation.